Students' Engagement in Learning English Language and its Interrelation with the Student-Teacher Relationship and the Students' Attitudes towards Learning the Language - Al-Zoubi, Rifa (Jordan Journal of Educational Sciences, 2013)
The study aimed at investigating students' engagement in learning the English language and its interrelation with the student-teacher relationship and the students' attitudes towards learning the language. In order to answer the questions of the study, the researcher constructed two scales; a scale to measure the students' engagement and another scale to measure the nature of the student-teacher relationship. As for students' attitudes towards learning English it was measured by a scale developed by Yamani (2008). A cluster random sample was chosen from first secondary students in Amman directorates, in which the sample consisted of (128) male students and (175) female students. The main results of the indicated study showed that students' engagement in learning English was at the medium level, there was no significant statistical difference at the level (α ≤ 0.05) between the male and female students' engagement level. However, the results showed that the students do have positive attitudes towards learning the English language, where significant statistical differences at the level (α ≤ 0.05) were found in favor of the female students. As for the student-teacher relationship, the fair and respect domains of the scale indicated that the students estimated their teachers as having a high degree of fairness and respect towards their students, however the teachers' sharing domain was estimated as being low. Significant statistical differences at the level (α ≤ 0.05) were found concerning the sharing domain and in favor of the male teachers, and in the fair domain in favor the female teachers. Moreover, the "caring and trust" domain explained 18% of the variance in students' engagement behavior, while students' attitudes explained 7% of it. As for teachers' respect, it explained 1% of the variance in students' engagement behavior.